Phenotypic variability and mutation hotspot in COX15‐related Leigh syndrome. Issue 6 (31st March 2020) - Halperin, Daniel; Drabkin, Max; Wormser, Ohad; Yogev, Yuval; Dolgin, Vadim; Shorer, Zamir; Gradstein, Libe; Shelef, Ilan; Flusser, Hagit; Birk, Ohad S.
Abstract: COX15 mutations were shown to underlie Leigh syndrome (LS), a progressive subacute necrotizing encephalopathy caused by defects in the mitochondrial respiratory chain. Here, two siblings of consanguineous kindred presented in infancy with a syndrome of hypotonia, nystagmus, psychomotor retardation, and pyramidal signs. Toward the end of their second year, both patients developed progressive quadriparesis, convulsions, and pseudobulbar palsy. Similar to two previously reported cases, one of the two affected siblings had severe hypertrophic obstructive cardiomyopathy, hearing loss, and no visual response. Through linkage analysis and whole‐exome sequencing, we identified a homozygous p.R217W mutation in Cytochrome C oxidase assembly protein COX15 homolog. Consistent with the known heterogeneity of mitochondrial diseases in general and that of LS in particular, several phenotypic features were markedly distinguished between the affected siblings and in relation to previous reports of COX15 mutations. Interestingly, of the previously reported five cases of COX15 ‐mutated patients, all of different ethnic origins, three had a p.R217W mutation. We highlight p.R217W as a hotspot mutation in COX15 and delineate the phenotypic variability, both between the patients we describe and in all cases reported to date.